Wzorzec osobowy czy wzorzec postępowania? Przyczynek do nowej definicji formułowanej z punktu widzenia historyka na przykładzie szlachty polskiej przełomu średniowiecza i czasów nowożytnych = - Świderska-Włodarczyk, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the context of historical research, the concept of role model is incongruent. For this reason, it should give way to the term model of decorum. Such a choice enforces the division of models of decorum into personal (formulated in relation to real persons) and impersonal (allegoric ones, concerning registers, sets, or lists of depersonalized traits ascribed to roles played and positions held). In such an understanding, every model of decorum is a real, available, and realized phenomenon, and simultaneously a mental fact embedded in the awareness of all times. As such it is a result of group and individual expectations.
Keywords: szlachta; wzorzec